2022
DOI: 10.1049/ntw2.12040
|View full text |Cite
|
Sign up to set email alerts
|

Agile roadmap for application‐driven Multi‐UAV networks: The case of COVID‐19

Abstract: Drones, also known as Unmanned Aerial Vehicles (UAVs), are about to bring drastic transformations to our world and daily lives. News thinking and efficient deployment are required to boost the adoption of UAV‐augmented commercial/civil applications. Yet, network service providers are still facing several design challenges of UAV‐assisted application, due to lack of a roadmap allowing to meet the target service level agreement requirements. In this paper, we propose a complete framework for the UAV as a service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Their case study in the Portland metropolitan area showed that the developed novel heuristic had a higher average energy consumption (around 30%) compared to the Gurobi, greedy, and 3SH algorithms, even though it achieved the best coverage in the shortest time. Therefore, several studies [59,64,[66][67][68]70] propose the design of healthcare logistics systems that include the use of drones. Some describe a model designed to achieve faster delivery times [68,70], while others focused on proposing a complete drone service framework, integrating all actors/stakeholders involved in the UAV service and outlining their interactions [64,66].…”
Section: Healthcare Logisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their case study in the Portland metropolitan area showed that the developed novel heuristic had a higher average energy consumption (around 30%) compared to the Gurobi, greedy, and 3SH algorithms, even though it achieved the best coverage in the shortest time. Therefore, several studies [59,64,[66][67][68]70] propose the design of healthcare logistics systems that include the use of drones. Some describe a model designed to achieve faster delivery times [68,70], while others focused on proposing a complete drone service framework, integrating all actors/stakeholders involved in the UAV service and outlining their interactions [64,66].…”
Section: Healthcare Logisticsmentioning
confidence: 99%
“…Therefore, several studies [59,64,[66][67][68]70] propose the design of healthcare logistics systems that include the use of drones. Some describe a model designed to achieve faster delivery times [68,70], while others focused on proposing a complete drone service framework, integrating all actors/stakeholders involved in the UAV service and outlining their interactions [64,66].…”
Section: Healthcare Logisticsmentioning
confidence: 99%
“…The article [ 35 ] proposed a comprehensive framework for the UAV as a service paradigm, bringing together all the actors/stakeholders involved in providing the UAV-augmented service and depicting their communication through data/service/money streams. The authors then apply their framework to the pandemics caused by viruses like SARS-CoV-2 and discuss how it can be used to enforce social isolation, spray disinfectants, broadcast warnings, transport medicine, and improve monitoring efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Together with monitoring human mobility [ 36 ], security personnel can provide people advice on how to avoid crowding, minimize one-on-one interaction, emphasize the value of social distance, etc. To perform these tasks, the authors of [ 37 ] used a drone swarm in a specific area. A camera and sensor were mounted on the ground to capture videos and a real-time view of that area.…”
Section: Applications Of Uavs During Covid-19mentioning
confidence: 99%
“…A standard approach for ensuring reliability is to provide an alternative channel between a particular destination and a given source via a group of UAV relays. Nevertheless, the great mobility and short battery lifespan of UAVs make such a system ineffective [ 37 ].…”
Section: Open Challenges Opportunities and Future Workmentioning
confidence: 99%